Cognitive resilience - quantifying cognitive performance loss following high-intensity motor-cognitive reactive agility exercises in high-level athletes - Jordao, B.; Hülsdünker, T. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study investigated cognitive resilience in response to a repetitive motor-cognitive reactive agility exercise in high-level athletes.